Oral manifestations in AIDS patients receiving antiretroviral therapy in a referral hospital in Peru - Ramos Tejada, Katherine Liset; Romero Gamboa, Julio César; La Serna, Paola (Horizonte Sanitario, 2022)
Objective: To determine the prevalence of oral manifestations in AIDS patients, under antiretroviral therapy in a referral hospital in Perú. Materials and methods: A prospective, not experimental, cross – sectional and quantitative study. There was a population consisting of 380 and a sample of 191 patients who met the selection criteria. The instrument was an adapted data collection form that consist of two parts, in one the personal data and in another the most frequent oral manifestations. Results: The prevalence of oral manifestations in AIDS patients under antiretroviral therapy in 59.50% with oral candidiasis being the most frequent with 35.5%, the prevalence of oral manifestations is higher in male gender with a 67% and in the age range between 18-25 years old in a 57%. Conclusions: There is a high prevalence of oral manifestations in patients with AIDS under antiretroviral therapy, the most frequent being oral candidiasis in males and in those under 25 years old. Key words: HIV-1; Antiretroviral; Viral load; T lymphocytes